2020
DOI: 10.1155/2020/9670360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Significance of Monocytes in Acute Stanford Type B Aortic Dissection

Abstract: Acute aortic dissection (AAD) is one of the most common fatal diseases noted in vascular surgery. Human monocytes circulate in dynamic equilibrium and display a considerable heterogeneity. However, the role of monocytes in AAD remains elusive. In our recent study, we firstly obtained blood samples from 22 patients with Stanford type B AAD and 44 age-, sex-, and comorbidity-matched control subjects. And the monocyte proportions were evaluated by flow cytometry. Results showed that the percentage of total CD14+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…Du et al also reported similar findings, compared with healthy controls, in a Chinese Han population (19). Another study on acute TBAD patients found that the percentage of CD14 + monocytes was significantly higher than that of normal volunteers, in which the percentages of the two monocyte subsets (CD14 bright CD16 − and CD14 bright CD16 + ) were increased significantly (P < 0.001) (16). Furthermore, selective depletion of monocyte/macrophage in mice model dramatically reduced the incidence of aortic dissection, supporting that monocytes/ macrophages have an important role in the pathophysiology of aortic dissection (27).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Du et al also reported similar findings, compared with healthy controls, in a Chinese Han population (19). Another study on acute TBAD patients found that the percentage of CD14 + monocytes was significantly higher than that of normal volunteers, in which the percentages of the two monocyte subsets (CD14 bright CD16 − and CD14 bright CD16 + ) were increased significantly (P < 0.001) (16). Furthermore, selective depletion of monocyte/macrophage in mice model dramatically reduced the incidence of aortic dissection, supporting that monocytes/ macrophages have an important role in the pathophysiology of aortic dissection (27).…”
Section: Discussionmentioning
confidence: 58%
“…Recruitment and activation of multiple inflammatory cells could lead to apoptosis of vascular smooth muscle cells, thus inducing wall fragility and subsequent aortic dilation, dissection, and even rupture (1,25). In this condition, the numbers and phenotypes of monocytes were significantly altered (16,26). A previous study demonstrated that classical monocytes were significantly increased in patients among the acute aortic dissection group compared with patients with carotid artery stenosis or subjects with traditional cardiovascular risk factors (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, monocytes and macrophages may work together in a certain relationship to promote AD. Furthermore, the data obtained by Lu et al suggested that monocytes might play an important role in type B AAD (BAAD) ( 56 ). In terms of mortality, the lower lymphocyte-to-monocyte ratio may be independently associated with the mortality of type A AAD (AAAD) ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…During centrifugation, the sample is centrifuged through the gradient, and the individual particles remain at the gradient density level that matches their own density. Frequently used solutions are Percoll [ 29 ], Ficoll [ 30 ], sucrose [ 31 ] and OptiPrep [ 32 ], the last of which was used in this study. Therefore, two different solutions were used and mixed together.…”
Section: Methodsmentioning
confidence: 99%